2015
DOI: 10.1016/j.stem.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Lipid Metabolism in the Forebrain Niche Suppresses Adult Neural Stem Cell Proliferation in an Animal Model of Alzheimer’s Disease

Abstract: Lipid metabolism is fundamental for brain development and function, but its roles in normal and pathological neural stem cell (NSC) regulation remain largely unexplored. Here, we uncover a fatty acid-mediated mechanism suppressing endogenous NSC activity in Alzheimer's disease (AD). We found that postmortem AD brains and triple-transgenic Alzheimer's disease (3xTg-AD) mice accumulate neutral lipids within ependymal cells, the main support cell of the forebrain NSC niche. Mass spectrometry and microarray analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
203
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(228 citation statements)
references
References 75 publications
(86 reference statements)
14
203
0
Order By: Relevance
“…We investigated the distribution of lactate within E9.5 embryos using matrix-assisted laser desorption/ ionization-imaging mass spectrometry (MALDI-IMS), a useful method for visualizing the spatial distribution of individual biomolecules at a spatial resolution of ∼30 µm pitch on intact tissues (Bailey et al, 2015;Hamilton et al, 2015;Sugiura et al, 2014). Fresh frozen embryos were sectioned and analyzed by MALDI-IMS.…”
Section: Transition Of Embryonic Metabolome Profiles During Cbmentioning
confidence: 99%
“…We investigated the distribution of lactate within E9.5 embryos using matrix-assisted laser desorption/ ionization-imaging mass spectrometry (MALDI-IMS), a useful method for visualizing the spatial distribution of individual biomolecules at a spatial resolution of ∼30 µm pitch on intact tissues (Bailey et al, 2015;Hamilton et al, 2015;Sugiura et al, 2014). Fresh frozen embryos were sectioned and analyzed by MALDI-IMS.…”
Section: Transition Of Embryonic Metabolome Profiles During Cbmentioning
confidence: 99%
“…Recent research (POLO-HERNANDEZ et al, 2014;ASTARITA et al, 2011;HAMILTON et al, 2015) has focused on the importance of oleic acid in the modulation mechanism of neural stem cell (NSC) transformation in neurons, neuron migration and synapse formation.…”
Section: Sgarbieri V C; Pacheco M T Bmentioning
confidence: 99%
“…Some lines of evidence have shown the occurrence of increased expression of the enzyme stearoyl-CoA-desaturase (SCD) in AD (ASTARITA et al, 2011). Hamilton et al (2015) identified a focus of lipid metabolism deregulation as a blocking mechanism in the reproduction of neural stem cells (NSC), resulting from Alzheimer's disease (AD). The authors demonstrated that interference in the signaling or synthesis of oleic acid blocked the proliferation of neural stem cells (NSC) in mouse models for AD.…”
Section: Sgarbieri V C; Pacheco M T Bmentioning
confidence: 99%
“…Continuing with this theme, Karl Fernandes (University of Montreal, Canada) showed that ependymal cells at the interface between the brain and cerebrospinal fluid (CSF) accumulate neutral lipids in Alzheimer's disease (Hamilton et al, 2015). The aberrant lipid droplet accumulation at the brain-CSF interface triggers the deterioration of the surrounding neural stem cell niche.…”
Section: Lipids and Neurodegenerationmentioning
confidence: 99%